2013
DOI: 10.1590/s1807-25772013000600003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tooth brushing supervision on the dental plaque index and toothbrush wear in preschool children

Abstract: OBJECTIVE: To evaluate the effectiveness of tooth brushing supervision in one or more sessions on dental plaque removal and toothbrush wear. MATERIAL AND METHOD: 3- to 5-year-old children received new toothbrushes and attended a puppet theater about oral health. Forty-nine children were randomly selected and divided into 3 groups (GI=20; GII=14; GIII=14). Fones' brushing method was demonstrated to the GI and GII groups to evaluate the following: the professional direct supervision and tooth brushing training i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
1
7
1
5
Order By: Relevance
“…The results showed that professional supervision in multiple sessions was effective in reducing plaque indexes, which were not influenced by brush damage, showing the need for continuous motivation for oral hygiene (12) .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results showed that professional supervision in multiple sessions was effective in reducing plaque indexes, which were not influenced by brush damage, showing the need for continuous motivation for oral hygiene (12) .…”
Section: Discussionmentioning
confidence: 95%
“…After two years of follow-up, the results revealed significant improvements in dental plaque scores with up to a 34% reduction in caries occurrence (14) . It is important to highlight that none of these studies (9,(11)(12)(13)(14) was developed by nurses. This demonstrates the need to strengthen and expand the integration of the nurse in health education activities in pre-schools, such as oral health, in addition to producing and disseminating knowledge related to the topic.…”
Section: Discussionmentioning
confidence: 99%
“…Though the cause of this phenomena is poorly understood, many suggestions have been proposed [5, 7–9, 9, 2630]. It is possible that, for example, as a child ages and his/her level of skill improves, he or she may develop effective tooth brushing skills [26, 27]; however, once ineffective skills are developed, it may be difficult for an adult to alter his or her established oral hygiene practices—i.e., an adult with an ingrained habit may have less learning plasticity as compared to a child or adolescent [31].…”
Section: Working Hypothesismentioning
confidence: 99%
“…Инструкции по чистке зубов должны соответство-вать познавательной способности и стадии развития детей [15,92].…”
Section: факторы оказывающие влияние на гигиену прunclassified
“…Sforza, L. Hogan, L. Wambier также не связывают степень износа щетки с ухудшением удаления зубного на-лета [45,78,92]. Они полагают, что значительно большее влияние на качество гигиены рта оказывают техника и продолжительность чистки зубов, а также сила давления на зубы в процессе чистки.…”
Section: эффективность зубной щетки в зависимости от степени износаunclassified